Against the Black Box. Issue 1 (1st June 2015) - Smith, Oliver
The Black Box is explored as a tool of power and control. Originating as a problem-solving tool in electrical engineering it is shown to have developed through its military and cybernetic use into an inherent part of technologies and knowledge, obscuring their origins and complexities. Although this process is often accepted as necessary, its hidden and unquestioned existence is shown to be problematic. The scale and complexity of the Black Box is discussed with reference to the large scale of historical computing and the distributed nature of infrastructural technologies as well as legal frameworks built around technologies. Through a number of examples, from networked consumer technologies to governmental surveillance techniques, the Black Box is shown to have opaque, leaky and talkative characteristics that contribute to its power.